A tributação da contraprestação paga pelo uso da imagem de artistas e esportistas - Marcondes, Rafael Marchetti (2016)
This work aims to examine taxation on compensation received by entertainers and sportspeople for the license granted to third parties to use their image rights. Current legislation approaches the matter in a generic way, either equating the use of an image right to a simple obligation to use or to an obligation to give or even not specifically regulating the subject. Therefore, we will present an investigative method by means of which it is possible to consistently decide whether or not to levy taxes in such operations. The proposal herein is to start examining the transaction concerning the use of an image by identifying the main activity agreed in order to subsequently evaluate if such rendering implies an obligation whose legal nature is either to do or to give. The conclusion for charging or not the various taxes will result from the comparison between each tax s material aspect and the legal nature of the analyzed obligation. Notwithstanding, we aim to previously define the characteristic features of personality rights, especially image rights, in order to be able to indicate the constitutional protection provided to the image in its several aspects: social image, sole external image and group external image, differentiating them from arena rights. The purpose is also to analyze distinctive features of the image, which make it a sole and unique right, as well as its legal nature from the several theories developed by the doctrine so as to define the parameters of the image. It is only after the abovementioned definition that this work will effectively examine the compensation gained by the image rights holder. The identification of the main activities involved and their legal nature will allow one to decide on the subsumption of facts concerning the use of the images of entertainers and sportspeople to the following taxes: Municipal Tax on Services (ISS), State Tax on Distribution of Goods, Transport and Communication Services (ICMS), Income Tax (IR), Social Contribution on Net Profits (CSL), Contribution for the Social Integration Program (PIS) and Contribution for the Financing of Social Security (COFINS), Contribution for Economic Intervention Royalties (CIDE-royalties) and Import and Export Duty. By examining the taxation by Income Tax, we will also analyze the possibility of entertainers and sportspeople to constitute legal entities aiming to exploit personal rights and the situations in which it is accepted to disregard the corporate entity. Finally, the paper will address the taxation regime applicable to international transactions comprising the use of the image of those entertainers and sportspeople, in situations which the purpose is an obligation to do and in those in which the purpose is an obligation to give, in compliance with OECD Model Convention and the treaties signed by Brazil in order to avoid double taxation